Experimental and numerical heat transfer investigation in turbulent square-duct flow through oblique horseshoe baffles - Skullong, Sompol; Thianpong, Chinaruk; Jayranaiwachira, Nuthvipa; Promvonge, Pongjet (My University, 2016)
An experimental and numerical work has been carried out to study the heat transfer enhancement in a heat exchanger square-duct fitted with 30° oblique horseshoe baffles (HB). In the current work, air is passed through the HB-inserted duct having a constant surface heat-flux. The air flow and heat transfer behaviors are presented for turbulent flow region, Reynolds number ranging from 4000 to 25,000. The pertinent parameters of the 30° HB elements include three relative baffle-pitches (PR=P/H=0.5, 1 and 2) and five relative baffle heights (BR=b/H=0.05, 0.1, 0.15, 0.2 and 0.25). Influences of those parameters on heat transfer and energy loss due to friction in terms of Nusselt number and friction factor, respectively are studied. The experimental result shows that at a given BR, the smallest pitch spacing (PR=0.5) provides the highest heat transfer and friction factor. The HB at BR=0.25 and PR=0.5 yields the highest heat transfer and friction factor but the one at BR=0.2 and PR=1 gives the maximum thermal performance. In addition, the thermal performance of using the HB is much higher than that of the wire coil insert, in comparison with other turbulators. To understand the heat transfer mechanism, a numerical inserted-duct flow simulation is also conducted and the obtained numerical results are in good agreement with measurements. Numerical flow and heat transfer behaviors such as streamlines, temperature and Nusselt number contours of the duct flow model are also reported.
Keywords: Horseshoe baffle; Inserted duct; Periodic flow; Thermal performance; Vortex generators